Hubungan Sistem Pengendalian Mutu Kantor Akuntan Publik dengan Etika Profesi dan Skeptisme Profesional Auditor - Cici Girik Allo; Yefta Andi Kus Nugroho (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This study aims to examine the relationship between KAP Quality Control System with professional ethics and professional skepticism of auditor in carrying out the profession as a professional accountant. The research method used includes correlational research. The study population was the auditor of KAP in Indonesia, amounting to 96 respondents. The data collection technique uses primary data in the form of a questionnaire distributed online. The results of this study indicate that the Public Accountant Firm's Quality Control System has a positive relationship with professional ethics and professional skepticism of auditor. The importance of implementing the Quality Control System in KAP to be more effective in controlling quality service results and understanding professional ethics and high skepticism in carrying out professional duties for auditor. This research is expected to be a reference for public accounting firms in improving performance and creating a good work environment for auditor.